2017
DOI: 10.18502/kls.v3i6.1119
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals, Antioxidant and Antifungal Properties of Acorus calamus, Curcuma mangga, and Allium sativum

Abstract: The purpose of this study to determine the content of phytochemicals, antioxidant and antifungal properties of the combination of Acorus calamus, Curcuma mangga, and Allium sativum. This research was descriptive qualitative, extractions were done by maceration method with ethanol with 3 different combinations (C1, C2 and C3). Phytochemical test reagent included 4 kinds of test, namely: alkaloids, flavonoids, triterpenoids, saponins and tannins. As for the antioxidant test, the method used was DPPH. The concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Unlike the previous studies, the inhibition zone test for Candida albicans produced the highest value on ethanol extract (3.72 mm/moderate) followed by n-hexane (3.32 mm/medium) and chloroform (2.22 mm/weak) (Muchtaromah et al, 2017). According to Chandra & Prasad (2017), differences in solvents could affect the results of phytochemical compounds drawn during extraction while the number and type of active compounds influenced the biological activity.…”
Section: Phytochemicalmentioning
confidence: 81%
See 1 more Smart Citation
“…Unlike the previous studies, the inhibition zone test for Candida albicans produced the highest value on ethanol extract (3.72 mm/moderate) followed by n-hexane (3.32 mm/medium) and chloroform (2.22 mm/weak) (Muchtaromah et al, 2017). According to Chandra & Prasad (2017), differences in solvents could affect the results of phytochemical compounds drawn during extraction while the number and type of active compounds influenced the biological activity.…”
Section: Phytochemicalmentioning
confidence: 81%
“…The level of 0.78% was the MBC value of all types of extract for both test bacteria, characterized by the absence of bacterial growth at all (colonies <0.1% of the original inoculum). Previous studies showed that concentrations of 0.39% and 0.78% were also the MIC and MBC values of calamus rhizoma extract against Candida albicans (Muchtaromah, 2017). Moreover it was known that the calamus rhizome extract effectively inhibited both gram positive and negative bacteria (broad spectrum) and fungi.…”
Section: Value Of Minimum Inhibition Concentration (Mic) and Minimum mentioning
confidence: 98%
“…The ethanol extract has the highest antioxidant activity may caused by the polar active substance of several antioxidant compounds contained within. The previous research proved that rhizome of jeringau extracted with ethanol has a group of antioxidant compounds such as alkaloids and triterpenoids (Muchtaromah, et al, 2017) where it can function as an antioxidant by donating hydrogen atoms in DPPH.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic microbes, free radicals can also cause infertility, thus antioxidant compounds are needed in neutralizing these free radicals. In previous study, active compounds that can be used as antioxidants and also contained in ethanol extract of jeringau are alkaloids and triterpenoids (Muchtaromah, et al, 2017). Hence this research aims to investigate the best solvent of Jeringau extract that produced the highest antioxidant and antifungi activities based on the polarity.…”
Section: Introductionmentioning
confidence: 99%
“…"Jamu Subur Kandungan" contains 15% garlic (Allium sativum), 15% rhizome of temu mangga (Curcuma mangga), 12% rhizome of jeringau (Acorus calamus), and other materials until 100%, which is well known as fertility enhancer. 7 Our studies have shown that spice blend of garlic (Allium sativum), temu mangga (Curcuma mangga) and jeringau (Acorus calamus) has high antioxidant activity and can be used as antifungal and antibacterial. 7,8 The containing spices in "Jamu Subur Kandungan" are individually considered as remedies for many diseases.…”
Section: Introductionmentioning
confidence: 99%